The Theory of the Mixing Of Uses in the Integral Urban Regeneration of Historical Centers (2000-2019) - Huatuco Jaimes, Cristhian (2021)
In this article, based on the academic context of the master's degree in urban regeneration, we seek to know the mix of uses framed in the integral urban regeneration of historic centers, where its evolution in these last 19 years is observed from the balance of the literature and theoretical discussion. In these last two decades, urban regeneration, the development of the mix of uses and the vision of historic centers have accentuated the change from a paradigm of urban character to one that focuses on human development specifically in the socioeconomic aspect, which it is demanding an increasingly comprehensive approach.